2016
DOI: 10.1177/2050640615590303
|View full text |Cite
|
Sign up to set email alerts
|

Argon plasma coagulation for the endoscopic treatment of gastrointestinal tumor bleeding: A retrospective comparison with a non‐treated historical cohort

Abstract: Endoscopic hemostasis of UGITB with APC has no significant impact on 30-day re-bleeding and mortality rates, irrespective of patient performance status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…6,12 Argon plasma coagulation is a noncontact thermal method of hemostasis that has been used to control bleeding from certain lesions in the GI tract and to debulk tumors for which surgery is not recommended. [17][18][19] Crespo Pérez et al published a report of using this technology to treat esophageal webs in a patient with PVS. 20 Of note, our patient had concomitant factor VII deficiency that hampered the use of argon plasma coagulation dilation.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 Argon plasma coagulation is a noncontact thermal method of hemostasis that has been used to control bleeding from certain lesions in the GI tract and to debulk tumors for which surgery is not recommended. [17][18][19] Crespo Pérez et al published a report of using this technology to treat esophageal webs in a patient with PVS. 20 Of note, our patient had concomitant factor VII deficiency that hampered the use of argon plasma coagulation dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes the results of those previous studies. The rate of immediate hemostasis with conventional ET in patients with acute UGIB from a malignant tumor was between 31 % and 100 % 6 12 13 14 15 16 17 18 . However, extensive effort and time are needed to achieve immediate hemostasis in patients with large bleeding tumors or oozing multifocal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Martins et al compared 25 patients with upper GI tumor bleeding who underwent APC with 28 patients who did not [21]. The study reported no differences in 30-day rebleeding (33.3% in the APC group vs. 14.3% in the control group; P=0.104) [22] (Table 1).…”
Section: Thermal Therapymentioning
confidence: 99%